The Concept of Memra in Targum Amos - Lier, Gudrun (Journal for semitics, 2020)
The Memra concept is notable in Aramaic Bible translation or Targum. In Targum Amos, the term is employed seven times in the Aramaic rendering of the Hebrew text of the prophet Amos. This study investigates how scholars interpreted the Memra concept in the context of earlier studies that focussed on the Pentateuchal Targums and the Former Prophets. It then ventures to establish how the notion of Memra is used in TJ Amos and how this compares with previous scholarly findings.